Breaking the glass ceiling: women’s perceptions of academic-scientific careers in physics and nursing - ANA REGINA G. BEZERRA; FERNANDA STANISCUASKI; MARCIA CRISTINA B. BARBOSA (Anais da Academia Brasileira de Ciências)
Abstract Women’s representation in science has grown, yet they still comprise only about a third of the global scientific community. While women are the majority in fields like social, biological, and health sciences, they remain underrepresented in others, such as exact sciences and engineering, from training stages to senior positions. Beyond gender-related challenges, motherhood introduces additional barriers. In this study, we analyzed the perceptions of research productivity fellows from the National Council for Scientific and Technological Development in the fields of physics and nursing regarding their academic-scientific trajectories. These fields present contrasting professional landscapes: women are a minority in physics and a majority in nursing. Data collected in 2020 from fellows active in 2019 revealed that being a woman and, in particular, being a mother impacts scientific careers differently across disciplines. In physics, participants perceived significant obstacles, including gender-based challenges and the disruption caused by motherhood. In nursing, however, motherhood was seen as more integrated into the academic journey. These findings underscore how the academic environment, shaped by the gender composition of a field, profoundly influences career experiences. Addressing these disparities requires context-specific strategies to create equitable and inclusive scientific environments.